2013
DOI: 10.1186/1471-2407-13-72
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c and HuR in ovarian cancer

Abstract: BackgroundMicroRNAs in solid malignancies can behave as predictors of either good or poor outcome. This is the case with members of the miR-200 family, which are the primary regulators of the epithelial to mesenchymal transition and have been reported to act as both oncogenes and tumor suppressors. This study assessed the role of miR-200c as regulator of class III β-tubulin (TUBB3), a factor associated with drug-resistance and poor prognosis in ovarian cancer.MethodsExpression of miR-200c was assessed in a pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 28 publications
1
87
0
2
Order By: Relevance
“…Most of the evidence comes from the work of Vasudevan and colleagues at the end of the past decade indicating a convincing direct relationship between the presence of specific miRNAs and the expression of a definite set of proteins. These noncanonical, positive effects of microRNAs seem to be delimited by a series of conditions, the most important being the growth condition (Vasudevan et al 2007) and the stress status of the cells (Prislei et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence comes from the work of Vasudevan and colleagues at the end of the past decade indicating a convincing direct relationship between the presence of specific miRNAs and the expression of a definite set of proteins. These noncanonical, positive effects of microRNAs seem to be delimited by a series of conditions, the most important being the growth condition (Vasudevan et al 2007) and the stress status of the cells (Prislei et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required in order to investigate and elucidate the complex mechanisms underlying the interaction between HuR expression levels and the response of patients to chemotherapy. Although numerous previous studies have reported that the expression of HuR in the cytoplasm has important roles in tumor aggressiveness, prognosis and the modulation of chemosensitivity-associated factors (6,8,28,31,32). It remains to be elucidated whether this is also true of nuclear HuR expression.…”
Section: Univariate Analysismentioning
confidence: 97%
“…These findings were concordant with the results of previous studies of other types of cancer (11,14). By contrast, it has also been suggested that increased HuR expression levels are associated with decreased sensitivity to CDDP in ovarian cancer (31). As aforementioned, CDDP is the principal agent in first-line chemotherapy (21,30).…”
Section: Univariate Analysismentioning
confidence: 99%
See 2 more Smart Citations